Electrical Tree Aging of Epoxy-Based Nanocomposites at Cryogenic Temperature. Issue 1 (March 2020) - Wang, Yongguang; Huang, Rongjin; Huang, Chuanjun; Wu, Zhixiong; Dong, Hongyu; Shen, Fuzhi; Zhang, Kaikai; Li, Xu; Li, Laifeng
Abstract: Electrical insulation at cryogenic temperatures is a key technology in the development of superconducting cables and superconducting current limiters. Due to their improved electrical, mechanical and thermal properties, the application of epoxy nanocomposites in high voltage power systems has shown a broad outlook. In this paper, tests were conducted to investigate the electrical tree aging phenomenon in epoxy resin/Al2 O3 nanocomposites in liquid nitrogen under AC voltages. The test samples were prepared with six levels of nanofiller content: 0 wt %, 1 wt %, 2 wt %, 3 wt %, 4 wt %, and 5 wt % by weight ratio. Experimental results showed that nano-fillers below 3% are easy to cause the electric field distortion at the needle tip, which reduces the tree inception voltage in the composite sample compared to that in the neat epoxy sample. At low temperature, the effect of electric field distortion on the tree inception voltage is significantly weakened and the tree growth rate decreases sharply with the increase of the content of the nano-filler.